PROYEKSI KARIER GEN-Z: MEMBANGUN ETIKA KERJA DAN PROBLEM SOLVING DALAM MENGHADAPI INDUSTRI 4.0 - Serli Nur Safitri; Nur Rizky Arya Fasha; Dhini Nurfitri Yani (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
The development of digital technology, automation, and internet-based system integration has brought the world into the era of the Industrial Revolution 4.0. This transformation demands human resource competencies that are not only technical in nature but also require mature soft skills preparation. This Community Service activity aims to improve the literacy and readiness of students at SMK Negeri 59 Jakarta in facing the challenges of the professional world through career projection education, strengthening work ethics, and developing problem-solving skills. The activity was implemented using a descriptive qualitative approach through interactive material presentation, independent simulation, group discussion, and structured program evaluation. The results of the activity indicate a significant increase in students' understanding regarding career projections in the digital era, the importance of professional integrity through good work ethics, and tactical issue resolution through problem-solving methods. Through this mentoring program, students are expected to be able to optimize their vocational competencies and remain adaptive to the global competitive climate of Industry 4.0.